Experimental study on the thermosiphon solution elevation pump with multiple lunate channels used in minitype solar air-conditionding system - Li, Zhengliang (2011)
A special structure thermosiphon solution elevation pump with multiple lunate channels used in minitype solar air-condition system was designed and experimentally measured on its elevating effects. Under the determinate operation conditions, its transient state performances were tested. The curves of the temperature and strong solution elevation volume with operating time were given out. Researches indicate that only 20 minutes is required from start-up to steady operation. Under the steady state conditions, the elevating rate of the strong solution and the distilled water yield rate versus the operating temperature were investigated. The minimum start-up operating temperature under different the immersing heights and the weak solution concentration were determined. The experimental results show that under the operating temperature condition of 85 °C, the strong solution elevation rate could reach 32 ml/s for 45% weak solution concentration. If all distilled water is evaporated, the refrigeration capability of the chiller can reach about 9 kW. At the same time, the heat transfer density of the lunate channel wall is about 10.2 kW/m2.